INVESTIGATING THE EFFECTS OF SOCIAL MEDIA ON THE WELL-BEING OF TEENAGERS: Received: 28th July 2022; Revised: 16th March 2023, 6th May 2023; Accepted: 11th May 2023 - Saraiji, Sara (PUPIL: International Journal of Teaching, Education and Learning, 2023)
There has been a positive association between screen time and depressive symptoms among adolescents. Research has found that using social media will increase self- comparisons especially if the engagement is passive. This would therefore increase the chances of depression and lower well-being. However, after investigating social media further, I found that the results were counter-intuitive and controversial on an individual level, especially for the youth. The objective of this work is to investigate the effect of social media on the well-being of teenagers. For this research paper, I asked many students to refrain from the use of social media for 33 hours and then tested their happiness score before and after. Then, I conducted a t-Test which showed a statistically significant difference in the mean of happiness scores before and after the experiment.